(untitled) - Khera, Harcharan Singh (Kuala Lumpur, 1976)
The oil palm industry has transformed rural livelihoods and landscapes across wide swathes of Indonesia and Malaysia, generating wealth along with economic, social, and environmental controversy. Who benefits and who loses from oil palm development? Can oil palm development provide a basis for inclusive and sustainable rural development?
Keywords: Ngành công nghiệp dầu cọ,Palm oil industry; Malaysia,Malaysia